Continuing Professional Education for Teachers and University and College Faculty. Issue 151 (September 2016) - Cranton, Patricia
Abstract : In this chapter, the author explores a variety of aspects of continuing professional education for teachers and university and college faculty members. She discusses the kinds of knowledge that are addressed and the role of online learning in continuing professional education.